No complete unknown – the saga of Bob Dylan’s literature nobel - Rollason, Christopher (The Grove - Working Papers on English Studies, 2016)
This essay examines the phenomenon of the award of the Nobel Prize for Literature for 2016 to the US singer-songwriter Bob Dylan (born in 1941) and the worldwide controversy it has given rise to. After consideration of the history of the campaign and the various classes of objection (categorial, aesthetic, individual-centred, hardline left and identitarian), it is concluded that, given also the quality of Dylan’s work, it is legitimate to award a Literature Nobel to a composer of songs.